The SAGE guide to writing in corrections - Hougland, Steven M.; Allen, Jennifer M. (Los Angeles : SAGE Publications, Inc, 2020)
"As part of the SAGE Guide to Writing series, The SAGE Guide to Writing in Corrections,1e, by Steven Hougland and Jennifer Allen, focuses on teaching students how to write in the academic setting while introducing them to a number of other professional writings specific to the correctional profession, such as the pre-sentence investigation report, contact sheets, court status reports, incident reports, rehabilitation and therapy. Covering correctional institutions as well as community corrections, the goal is to interweave professional and technical writing, academic writing, and information literacy, with the result being a stronger, more confident report writer and student in corrections. This text will be a concise supplemental writing book in courses focused on writing in the criminal justice discipline, report writing, or in introductory corrections courses. It is part of a series of books on this topic that will span criminal justice, policing, corrections, and research methods"--
Includes bibliographical references : pages 135-139).
Keywords: Criminal justice, Administration of -- United States -- Authorship; Criminal justice, Administration of -- Research -- United States; Legal composition -- United States; Report writing -- United States